AIDS : opposing viewpoints - Biskup, Michael D., 1956-; Swisher, Karin, 1966- (Opposing viewpoints series (Unnumbered), 1992)
Includes articles that present different viewpoints on such aspects of AIDS as the seriousness of the problem, moral issues, prevention, and treatment. Includes critical thinking activities.